The Motet in England in the Fourteenth Century - Lefferts, Peter (Michigan UMI, 1983)
The history of polyphonic music in late medieval England is difficult to reconstruct on account of the paucity of intact sources, the concomitant lack of a substantial number of complete pieces, and the difficulty with which the surviving repertoire can be associated with any specific institutions or social milieu~ Nonetheless, there are significant scattered remains, and this study endeavors to examine in detail one important genre, the motet, in light of all surviving music, placing a great deal of weight on the analysis of fragments. The evidence suggests that the motet was cultivated for the larger abbeys and monastic cathedrals, primarily Benedictine, Cistercian, and Augustinian houses.It was a sacred genre, and in typical larger collections there was probably provision of a motet for all major feasts of the Temporale and Sanctorale, though the precise role of the motet in the liturgy, whether as an interpolation or as a direct substitute for ritual plainchant, is not yet established. The thesis is organized in four large chapters and two appendices. Chapter One discusses the validity of the temporal limits imposed on the thesis (ca.1300-1400) , the problems of the definition of the motet genre and its function, and the problem of establishing a chronology for sources and individual pieces. Chapter Two establishes a typology for motet structures; demonstrating that the English intensely cultivate a few clear archetypes for motet form in the earlier part of the century, producing pieces of high musical interest and fascinating detail, and showing also that indigenous features were not entirely eradicated under French influence in the latter half of the century. The third chapter reviews the notational systems that developed in England in the 14th century, both in relationship to earlier English mensural notations and also to contemporaneous continental systems. The fourth chapter discusses features of the motet texts, concentrating on subject matter, sources and models for text language, and certain aspects of versification. A lengthy first appendix contains critical reports, texts, and transcriptions for most of the 14th-century repertoire; a short second appendix lists the 13th-century English motet repertoire with two transcriptions.
Submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in the Graduate School of Arts and Sciences Columbia University, 1983
Keywords: Middle Ages (500-1400); Motet; Music history; United Kingdom